Curricular proposal for the strengthening of life skills in high school students (Innovaciones Educativas, 2020)
Facing the need to offer a proposal which facilitates tools for the improvement of quantitative and communicative qualities in high school students of high schools located in coastal and border areas in Costa Rica, this paper presents the research process carried out by putting forward an interdisciplinary curricular proposal for the strengthening of communicative and quantitative skills. This was based on the World Health Organization’s Life Skills approach, which supports the didactic units’ proposal. The approach for the development of this proposal was an action-research methodology. Teachers of Mathematics and Spanish participated in workshops for the planning of units. Later, these units were put into use with the students, and the process was evaluated through blogs and interviews with the teachers. The characteristics and skills developed in the proposal are exposed in the analysis of the results, and on the basis of this study along with its application process. In conclusion, this proposal provides a collaborative planning methodology that allows teachers to innovate their practice by offering context-oriented units
Keywords: Life skills; Mathematics; Spanish; curriculum design; secondary education